Buddhist Interpretations Through Physical and Metaphysical Speaking of Buddhadasa Bhikku - Khantiwanno (Yimsangum), Phraprasit (Journal of Graduate MCU KhonKaen Campus, 2022)
Buddhadasa Bhikkhu is known as the "Nakarchun of Theravada" because he studies analytical Buddhism from Tipitaka and applies doctrine to life. He states religion and life as the same thing. Subjects that study religious interpretations are called "Hermeneutics ", they are described into two characteristics: 1) traditional interpretation, which is interpreted in succession, which has interpretations, interpretations of sentences, interpretations of texts, interpretations of narratives, interpretations to eliminate ignorance, and 2) interpretations to satisfy curiosity, it is an analytical interpretation to find the substance of the word. Buddhadasa Bhikkhu uses a method of critical interpretation in his teaching. It is divided into two languages: 1) human language is a common language, 2) Dhamma language is a language used to communicate Dhamma, such as "Buddhism". Dhamma refers to the true virtues or attributes of constantly awake people. In addition, Buddhadasa Bhikkhu interprets criticism, such as the study of the dog tail. It refers to education that provides only knowledge but does not provide intelligence, so it is an imperfect study.